Documentation and dissemination of scientific evidence by the Uganda Public Health Fellowship Program: experiences and lessons learnt, 2015-2020 - Lilian Bulage; Alex Riolexus Ario; Steven N. Kabwama; Benon Kwesiga; Daniel Kadobera; Christine Kihembo; Simon Antara; Rhoda K. Wanyenze (BMC, 2021)
Abstract Background During participation in Field Epidemiology Training Programs (FETP) residents/fellows generate scientific evidence from the various public health projects they are engaged in. However, this evidence is not sufficiently disseminated to influence policy and practice. We describe the processes through which evidence is disseminated, and share achievements and lessons learnt during the first 5 years of the Uganda Public Health Fellowship Program (PHFP). Methods The PHFP is a 2-year, full-time, non-degree fellowship, and the first post-masters FETP in Africa for mid-career public health professionals. Fellows gain competencies in seven main domains, which are demonstrated by deliverables while learning through service delivery, 80% of the time within Ministry of Health and related agencies. Generated public health evidence is disseminated immediately through sharing of daily situation reports with the National Task Force for Epidemic Preparedness and Response, as well as regional and district levels. Information is also disseminated on an intermediate to long-term basis through newspaper articles, epidemiological bulletins, abstracts and conference presentations, and publications in scientific journals. Results During 2015-2020, PHFP enrolled 80 fellows in seven cohorts, including five of whom who had graduated. Overall, 355 field projects had been implemented. Additionally, PHFP made 287 conference presentations including 108 international and 178 national conferences. Altogether, the Uganda PHFP has received 7 awards, 4 of these for excellent scientific presentations during conferences. By end of 2020, PHFP had written 147 manuscripts at different stages of peer review, including 53 publications; and published 153 epidemiological bulletins. Dissemination performance was limited by delays due to challenges like non-adherence to product clearance guidelines, limited persons to conduct product review, and limited expertise on certain scientific areas, authorship related issues, and competing priorities among fellows, staff, and alumni. Conclusions The PHFP has disseminated public health evidences through various means to a wider range of audiences within Uganda and globally. Manuscript publication and monitoring of actions taken as a result of evidence dissemination is still limited. We recommend putting in place mechanisms to facilitate publication of all scientific evidence and deliberate efforts to ensure and monitor scientific evidence utilization.